Mycobacterium tuberculosis and avium complex investigation among Malaysian free-ranging wild boar and wild macaques at wildlife-livestock-human interface - Lekko, Yusuf Madaki; Che' Amat, Azlan; Peck, Toung Ooi; Omar, Sharina; Ramanoon, Siti Zubaidah; Mazlan, Mazlina; Abdullah, Faez Firdaus Jesse; Jasni, Sabri; Abdul Razak, Mohd Firdaus Ariff (MDPI, 2021)
Wild animals are considered reservoirs, contributing to the transmission of emerging zoonotic diseases such as tuberculosis (TB). A cross-sectional study was conducted by opportunistic sampling from fresh carcasses of free-ranging wild boar (n = 30), and free-ranging wild macaques (n = 42). Stained smears from these tissues were tested for acid fast bacilli (AFB) with Ziehl–Neelsen staining. Mycobacterial culture was conducted using Lowenstein–Jensen media and Middlebrook 7H11 agar media. Polymerase chain reaction (PCR) was performed through the detection of the 16S rRNA gene, with multiple sets of primers for the detection of Mycobacterium tuberculosis complex (MTBC) and Mycobacterium avium complex (MAC). In wild boars, 30% (9/30; 95% Confidence Interval: 16.7–47.9%) of examined samples showed gross tuberculosis like lesions (TBLLs). Multiple nodular lesions that were necrotic/miliary with cavitation were found in the submandibular lymph nodes, tonsils, lungs, kidney and liver, while single nodular lesions were found in the mediastinal lymph nodes, spleen and mesenteric lymph nodes. Conventional PCR on the submandibular lymphoid tissues of wild boar (nine samples with TBLLs and three non TBLL samples) showed that 75% (9/12) were positive for Mycobacterium bovis (95% CI: 46.8–91.1), and 91% (CI: 64.6–98.5) were positive for Mycobacterium avium. For macaques, 33.3% (10/30) were positive for M. avium (95% CI: 19.2–51.2) but negative for MTBC.